Pengaruh Internal Branding dan Brand Commitment terhadap Organizational Citizenship Behavior (OCB) (Studi pada Dosen Universitas Negeri Surabaya) - Tanisa Arsya Soepardjo; Dewi Tri Wijayanti; Jun Surjanti (Jurnal Ilmu Manajemen, 2020)
Organizational citizenship behavior is valued as work-related behavior that is not related to the formal organizational reward system, and, in aggregate, encourages the effective functioning of the organization. This is shown from some data obtained that the teaching staff or lecturers of Universitas Negeri Surabaya (Unesa) from the existing basic tasks and functions, which consists of research and social services, are considered not enough to be done only during working hours. Therefore this study sees that OCB is conducted by a Unesa's lecturers. This study aims to determine the effect of Internal Branding and Brand Commitment on Organizational Citizenship Behavior for teaching staff. This research uses a quantitative approach, using the questionnaire method by determining accidental sampling. The formulation of the technique used in this study is multiple linear regression analysis. Through multiple linear regression analysis techniques, the findings in this study answer the research hypothesis between ain, (1) the influence of Internal Branding on Organizational Citizenship Behavior of teaching staff at Unesa has a positive impact, the coefficient results showed 0.183 (0.000 <0.05), then the first hypothesis test accepted, (2) Effect of Brand Commitment on Organizational Citizenship Behavior has a positive effect, with a coefficient result of 0.44 (0,000 <0.05) then the results of the second hypothesis test are accepted, (3) Effect of Internal Branding and Brand Commitment on Organization Citizenship Behavior is stated Significantly, the F-count results show 136,299 (0,000 <0.5) then the results of the third hypothesis test are accepted.